State of Psychological well-being of students during Lockdown due to Covid-19 Pandemic: view from some selected parts of India - Rahman, Mustafizur; De, Sukanya (Green University Review of Social Sciences, 2022)
Well-being refers to the state of being relaxed, healthy or joyful. It is not only about physical health but also concerns a great deal with psychological and social aspects. This study attempts to find out the relation between Covid-19 and state of psychological well-being of students and whether the lockdown had a positive or negative impact on them. This study is administrated by survey method and Google Form is used for the comprehension of the impact. A total of 123 students from 22 states of India have participated in this study. The study finds that the pandemic has left the students anxious and worried about their future. The lockdown due to Covid-19 pandemic is making them apprehensive and stressed; hence, maintaining mental well-being is also a concern for them. While the entire world is under the fear of falling ill, for the students in India the worry about their jobs and career is greater than that of falling physically ill. The results also indicate that at the initial stage, the students were happy about the lockdown and enjoying their free time at homes, but eventually, they started getting frustrated. They also started spending most of their time on screens, being highly active on social media, mobile, computer, and TV screen which has some side-effects on students’ psychology. Green University Review of Social Sciences Dec 2021; 7(1-2): 188-200